The Impact of Human Capital on Stratigic agility " Field Study in Jordan tourist companies" - الروسان محمد; العموش مثنى (Journal of Economics and Administrative Sciences, 2017)
The research aims to identify the degree of the availability of knowledge, skill and ability as components of human capital, in addition to stand at the level of strategic agility upon tourism and travel agencies company of Jordan, the impact of human capital on strategic agility has been tested through distribution of a questionnaire on a Randomly Sample from Workers in Jordan tourist Companies of (349),a number of statistics techinces have been used simple liner Regrision and Multiplayer regession, it has shown that the degree of knowledge, ability and skill availability was high, and the same applies on strategic agility components, and shown out that there is a statistically significant impact between human capital and strategic agility, upon that, a number of recommendations have been offered.Concertrated Mostly on training Process, development, Know ledge, Skills and Capailities, monitoring and diagnosing opportunities and threats and the ability to deal with them.